Chitosan degradation products promote healing of burn wounds of rat skin - Zhang, Chuwei; Zhang, Qingrong; Yang, Dongmei; Qiao, Yating; Wang, Bolin; Yan, Jun; Li, Zihan; Huang, Zhanghao; Zhou, Youlang; Hu, Kesu; Zhang, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Burns can impair the barrier function of the skin, and small burns can also cause high mortality. The WHO has described that over 180,000 people die of burns worldwide each year. Thus, the treatment of burn wounds is a major clinical challenge. Chitooligosaccharides (COS) are alkaline amino oligosaccharides with small molecular weights obtained by enzyme or chemical degradation of chitosan. With the characteristics of biocompatibility, water solubility and degradability, it has attracted increasing attention in the fields of biomedicine. In the present study, we used COS to treat deep second-degree burn wounds of rat skin and found that COS was able to promote wound healing. We also revealed that COS could promote fibroblast proliferation. Transcriptome sequencing analysis was performed on COS-treated fibroblasts to identify the underlying mechanisms. The results showed that COS was able to promote wound healing through regulation of the mitogen-activated protein kinase (MAPK) pathway and growth factor Hepatocyte Growth Factor (HGF). Our results provide a potential drug for burn wound therapy and the related molecular mechanism.